A Manual of Egyptian Pottery Volume 3 : Second Intermediate Through Late Period. - Wodzinska, Anna (AERA Field Manual Ser., 2009)
This is the third volume in a four-book set covering all Egyptian pottery, ranging from the earliest (Fayum A) ceramics to pottery made in Egypt today, organized by historical periods. The manuals are quick identification guides as well as starting points for more extensive research. For each period, ceramic types are illustrated with a line drawing, accompanied by a description that includes information on the pot's material, manufacturing techniques, surface treatment, and shape. Color plates of representative ceramic types are included to give the clearest sense of the color, composition, and surface treatment. All four volumes provide an extensive list of suggested readings as well as a bibliography for each period. Introductory chapters in each book discuss the basics of pottery manufacture and analysis. The first comprehensive guide to Egyptian pottery, this set will prove valuable to students as well as experienced field archaeologists. The volumes come in paperback and spiral-bound versions. The spiral bound versions, with hard laminated covers and tabs, are designed especially for the field and lab.